ON THE THEORETICAL APPROACHES TO THE CLASSIFICATION OF INNOVATIVE ACTIVITY OF BUSINESS STRUCTURES - V. A. Vernikov (Модернизация, инновация, развитие, 2015)
Innovative activity of business structures, an important part of their capacity strategically sustainable and competitive development. In the literature there are many definitions and theoretical approaches to the classification of innovative activity of enterprise structures. As classification bases used some combination of features and qualities, but in fact the classification are largely biological and behavioral analogy. In this article, an attempt to create a classification of innovative activity of enterprise structures